"CLICKable" azide-functionalized phosphonates for the surface-modification of molecular and solid-state metal oxides. Issue 41 (12th September 2016) - Schönweiz, S.; Knoll, S.; Anjass, M.; Braumüller, M.; Rau, S.; Streb, C.
Abstract : A bifunctional phosphonate azide tether is reported which enables surface modification of molecular and solid state metal oxides as well as subsequent modification by CLICK chemistry. Abstract : The covalent functionalization of metal oxide surfaces with organic ligands gives unique organic–inorganic hybrids. Here we report a bifunctional organic tether combining a phosphonate for metal oxide anchoring with an organic azide for attachment of organic groups. Stable binding of the tether to molecular and solid-state metal oxides is demonstrated and the subsequent "CLICKability" of the TiO2 -anchored tether is shown. The phosphonate-azide reported could in future allow the general linkage of functional organic groups to metal oxides.